1983
DOI: 10.1287/inte.13.6.116
|View full text |Cite
|
Sign up to set email alerts
|

Operations Management Literature: Publications on Real-World Applications

Abstract: A framework for classifying real-world applications of operations management is presented. Based on a survey of eight periodicals, the nature of and lacunae in field-based research are pointed out. The paper also discusses the politics of publishing and some measures for enhancing the number of articles related to actual applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1988
1988
1999
1999

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Twenty years ago, Gupta (1971) declared the theoretical solutions of scheduling problems so prominent in OM literature to be "of no appreciable use to practising schedulers". A dozen years on, Lingaraj and Raiszadeh (1983) found in their survey of eight OM journals that less than a quarter of all the articles were real world applications, and that 26 per cent of those were on scheduling. In their update of the OM research agenda, Amoaka-Gyampah and investigated the contents of major OM journals and concluded, "current research is not much different from pre-1980 research in terms of orientation and emphasis".…”
Section: The Academic/practitioner Gap In Ommentioning
confidence: 99%
“…Twenty years ago, Gupta (1971) declared the theoretical solutions of scheduling problems so prominent in OM literature to be "of no appreciable use to practising schedulers". A dozen years on, Lingaraj and Raiszadeh (1983) found in their survey of eight OM journals that less than a quarter of all the articles were real world applications, and that 26 per cent of those were on scheduling. In their update of the OM research agenda, Amoaka-Gyampah and investigated the contents of major OM journals and concluded, "current research is not much different from pre-1980 research in terms of orientation and emphasis".…”
Section: The Academic/practitioner Gap In Ommentioning
confidence: 99%
“…Over 20 years ago Gupta[17] declared the theoretical solutions of scheduling problems, which were so prominent in OM literature, to be “of no appreciable use to practising schedulers”. A dozen years on, Luigaraj and Raiszadeh[18] found in their survey of eight OM journals that less than a quarter of all the articles were real‐ world applications, and that 26 per cent of those were on scheduling. Swamidass[19], like Meredith et al [20], found that the focus of published research had changed little by 1987.…”
Section: The Academic/practitioner Gap In Operations Managementmentioning
confidence: 99%